فاعلية نموذج تدريسي قائم على التعلم النشط في تطوير الكفاءة الحركية لدى طلاب المرحلة الإعدادية في دروس التربية البدنية (Comprehensive Journal of Science, 2026)
This study aimed to investigate the effectiveness of an active learning–based instructional model in developing motor competence among preparatory school students in physical education classes. A quasi-experimental design with pre- and post-measurements for experimental and control groups was employed. The sample consisted of 45 eighth-grade students from Khaled Bin Al-Walid Basic Education School, Surman, Libya, during the first semester of the 2025–2026 academic year. The students were divided into an experimental group (n = 23), which received the active learning instructional model, and a control group (n = 22), which was taught using the traditional method.The research instruments included standardized motor competence tests (balance, muscular strength, speed, coordination, and throwing–catching skill) and a motivation and participation questionnaire. The findings revealed statistically significant differences at (α ≤ 0.05) between the pre- and post-tests of the experimental group in favor of the post-test. Significant differences were also found between the experimental and control groups in the post-test in favor of the experimental group.The results indicate that the active learning–based instructional model effectively enhances motor competence, motivation, and active participation compared with traditional teaching methods. These findings highlight the importance of integrating interactive learning strategies into physical education curricula at the preparatory stage.
Keywords: Active Learning, Instructional Model, Motor Competence, Physical Education, Preparatory Stage